Hemodynamic Effect of the Last Finishing Coils in Packing the Aneurysm Neck - Wan, Hailin; Lu, Gang; Huang, Lei; Ge, Liang; Jiang, Yeqing; Li, Gaohui; Leng, Xiaochang; Xiang, Jianping; Zhang, Xiaolong (Frontiers in Neurology, 2020)
Background Using the finishing coils to densely pack the aneurysm neck is necessary. However, the exact hemodynamic effect of finishing coils in packing the aneurysm neck is unknown. Objective To evaluate the hemodynamic characteristics of finishing coils to densely pack the aneurysm neck, using finite element method (FEM) simulation. Methods Computational study was performed based on a 44-year-old female patient with an unruptured wide-necked carotid-ophthalmic artery aneurysm treated with LVIS stent-assisted coil embolization. Four computational fluid dynamics (CFD) models including pre-treatment, post-stenting, common stent-assisted coil embolization (SACE), and common SACE with finishing coils were evaluated qualitatively and quantitatively. Results Compared with the baseline of pretreatment model (100%), sac-averaged velocity in post-stenting, common SACE, and common SACE with finishing coils models decreased to 95.68%, 24.38% and 13.20% respectively, high flow volume (> 0.1 m/s) around the aneurysm neck decreased to 92.19%, 9.59% and 5.57% respectively, mean wall shear stress (WSS) increased or decreased to 107%, 30.86% and 23.89%. Conclusion Finishing coils to densely pack the aneurysm neck can generate favorable hemodynamic modifications, which may decrease the recurrence.